Comparative analisys of vertical and horizontal static interaction forces between track and magnetic suspension vehicle - Frishman, Ye. M.; Umanov, M. I. (Science and Transport Progress, 2012)
In the article an analysis of interrelation of vertical and lateral interaction forces acting in the magnetic suspension system having permanent magnets of rectangular cross section with the constant (throughout the magnet volume) value of magnetization vector is performed. It is found that the increase in the magnetic bend width (for track and vehicle) leads to improving the lateral stability index as well as reducing the elevating power and the magnetic suspension efficiency.